A Multimethod Examination of the Dynamics of Recidivism During Reentry. Issue 1 (2nd January 2016) - Rydberg, Jason; Grommon, Eric
ABSTRACT: Research on prisoner reentry has indicated that the transition to the community can be a tumultuous process. Despite this growing understanding, research has continued to operationalize recidivism as a terminal event in the reentry experience, categorizing returning prisoners as recidivists and nonrecidivists. Using detailed mixed methods with a small cohort of parolees, this inquiry documents the dynamic nature, timing, and context of recidivism as it occurs during reentry. The analyses suggest that treating initial recidivism events as if they were terminal to reentry has the potential to miss information about subsequent reentry processes and outcomes. Comparing multiple recidivism measures with supervision outcomes suggests that simple categories of recidivists and nonrecidivists may not be informative for the purposes of reentry research.